Analysis Of Local MSME Community Business Models Towards MSME Sustainability: An Nvivo Approach To Understand Business Perceptions And Practices - Reni Ria Armayani Hasibuan; Nur Fadhilah Ahmad Hasibuan; Nurhayati; Ahmad Wahyudi Zein (LP2M IAIN Palopo, 2025)
This study analyzes the business model of local MSME communities in supporting business sustainability in Medan City. The main focus is on the strategies implemented by MSME communities to enhance the competitiveness and sustainability of their members' businesses, as well as the challenges faced in adopting sustainable business models. This research employs a descriptive qualitative method with a case study approach. Data were collected through in-depth interviews, direct observations, and document analysis. Data analysis was conducted using NVivo 12 Plus software with the Miles and Huberman model, including data reduction, data presentation, and conclusion drawing. The findings indicate that MSME communities such as Bazar Orang Medan (BOM), Rumah Kawan Bunda (RKB), and About Women Community (AWC) play a significant role in supporting their members' business sustainability through digital marketing, business management training, and access to networks and resources. The business strategies implemented are based on the Triple Bottom Line (TBL) approach, covering economic, social, and environmental aspects. However, the environmental aspect has not been fully integrated into MSME business practices. The MSME community acts as a catalyst for business desires, and further synergy is needed between the government, society, and business actors to develop more sustainable business strategies.